(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
High performance thin layer chromatography (HPTLC) offers many advantages over HPLC. It reduces the cost of analysis as compare to HPLC. The mobile phase consumption per sample is extremely low in HPTLC, hence reducing the acquisition and disposal cost. Considering the cost and suitability of analysis for estimation of zolpidem tartrate in bulk and its marketed formulation, HPTLC method was developed and validated. The Camag HPTLC system, employed with software winCATS (ver.1.4.1.8) was used for the proposed analytical work. Planar chromatographic development was carried out with the help of Silica Gel 60 F254 precoated TLC plates. Sample application was facilitated by Linomat 5 applicator. After sample application plates were subjected for ascending development in twin trough chamber of 10×10 dimension, using 10 ml of solvent system. The optimised mobile phase was composed of ethyl acetate: methanol: acetonitrile (7:1.5:1.5 v/v/v). In post- development, the plates were air dried and then scanned densitometrically using a UV detector at 298 nm in absorbance mode. In HPTLC densitogram well defined peak was obtained for zolpidem tartrate with peak start position at 0.55 Rf , max position at 0.59 Rf and end position at 0.63 Rf. The optimal Rf value for zolpidem tartrate was found to be 0.58. Performance characteristics of HPTLC method for estimation of zolpidem tartrate in bulk and its marketed dosage form were statistically validated as per the recommendations of ICH guidelines of analytical method validation. The HPTLC method was found to be linear across the range 200- 800 ng/spot. The LOD and LOQ values were found to be 16.99 and 51.50 ng/spot respectively. The method was found to be accurate, precise, robust and economical for the analysis of zolpidem tartrate from bulk and its formulation.